Contribuições para um estudo psicossocial da educação do campo - Oliveira, Ariane Angelita de (2015)
This dissertation aims to discuss the role of both the founding and the normative documents of Rural Education for the generation, transformation and consolidation of social representations about this object. A brief history of the Rural Education Movement in Brazil was presented, explaining its relationship with the social movements and the school. Next, some considerations about the Social Representations Theory were presented, emphasizing its principles and its contributions in addressing the knowledge embedded in Rural Education. The next step comprised the organization of the research corpus, by selecting the documents that would be analyzed and organizing them into two groups: founding documents and normative documents of Rural Education, each one with two subgroups: national and state documents. In this research, founding documents comprise the texts and discourses (letters, manifestos, declarations) elaborated by social movements and by the National Forum of Rural Education. To analyse the foundation documents, semantic schemes were drawn, highlighting and linking the main ideas, to understand their meanings. Afterwards, the IRAMUTEQ software was used. This is a free statistical package for text analysis, developed by Pierre Ratinaud (2009). Similitude analyses were carried out to observe the connections between words, based on co-occurrences; the Descendent Hierarchical Classifications Analysis (CHD) organized the textual information, by classifying the text segments according to their vocabulary and finally, the Lexicographic Analysis calculated the frequencies of the active and supplementary forms. On the normative documents, just the lexicographic analysis was carried out, to compare the lexical forms of both groups of documents. The analyses showed that the foundation documents accomplish the communicative function of propagating the representations about Rural Education around nuclear elements such as: a new project of society; the Countryside as a territory; the countryside populations as people of the countryside, recognizing their ethnic and cultural diversity; the public education of quality as a right; the ethical, political, scientific and technological formation, respecting the culture of each community and the teachers' training aligned with those representations and objectives. The state founding documents show little concern on stressing the culture and the diversity of the peoples of the countryside and, in the normative documents, this term disappears. In the state normative documents, there is a strong tendency to equalize the concept of Rural Education with Education in the countryside, or rural education, with emphasis on the professional training and emptying of the political and cultural dimensions, which are essential for the affirmation of the countryside population as People of the Countryside. Last, it is discussed the possibility of those documents influencing the generation and the transformation of social representations in the municipalities and schools that are not yet actively engaged in the social movements that have been fighting for 18 years for the acknowledgement and implementation of the project of Rural Education.